Influences of dietary protein sources and crude protein levels on intracellular free amino acid profile in the longissimus dorsi muscle of finishing gilts. Issue 1 (December 2015) - Qin, Chunfu; Huang, Ping; Qiu, Kai; Sun, Wenjuan; Xu, Ling; Zhang, Xin; Yin, Jingdong
Abstract Background The current study was carried out to determine effects of dietary protein source and crude protein (CP) level on carcass characteristics, meat quality, and muscle amino acid (AA) profile in finishing gilts. The experiment was designed as a 2 × 2 factorial arrangement with two sources of dietary proteins (cottonseed meal, CSM vs. soybean meal, SBM) and two levels of CP (12 % vs. 14 %, as-fed basis). Seventy-two crossbred gilts (89.5 ± 0.9 kg) were allotted to one of four dietary treatments in a randomized complete block design for a period of 28 d. All diets were formulated to be isoenergetic and similar concentrations of standardized ileal digestible essential AA covering the nutrient requirements of pigs. Results Growth, carcass characteristics and meat quality were not affected by dietary protein source nor crude protein level (P  > 0.10) except that average daily feed intake was increased by CSM diets (P  = 0.03). Gilts offered reduced protein diets had lower muscle pH45min (P  < 0.05). Neither dietary protein source nor crude protein level influenced N deposition. However, reduced protein diets decreased N intake, N excretion, and serum urea nitrogen content, whilst improved N efficiency (P  < 0.01). CSM diets increased N intake (P  = 0.04), but did not depress N efficiency. The concentrations of phenylalanine, tryptophan, cysteine and tyrosine (P  < 0.05) of thelongissimus muscle were decreased when gilts offered CSM diets, while muscle intracellular free valine concentration was increased (P  = 0.03). The gilts offered reduced protein diets had greater intracellular concentrations of free methionine, lysine, and total AA in muscle (P  < 0.05). Conclusion These results suggest that CSM could replace SBM as a primary protein source in finishing pig diets in terms of performance, N efficiency, carcass characteristics, and meat quality, but decrease the concentrations of muscle specific AA. Furthermore, the reduced protein diet played an important role in increasing muscle intracellular concentrations of specific free amino acids (FAA), and in reducing the relative ratios of specific FAA to lysine inlongissimus dorsi muscle of pig, whose biological meaning needs further studies.